Gastric Negative Pressure Suction Method Reduces the Incidence of PONV after Orthognathic Surgery - Wang, Jia; Zhang, Zhenzhen (Frontiers in Surgery, 2022)
Objective To investigate the effect of gastric negative pressure suction on the incidence of postoperative nausea and vomiting (PONV) in patients undergoing orthognathic surgery. Methods A retrospective study of 772 patients who underwent orthognathic surgery from October 2016 to January 2021 was performed, excluding possible confounding factors. The patients were divided into a negative gastric suction group (group 1) and a group without gastric suction (group 2), according to whether gastric suction was used after general anaesthesia. There were 386 patients in each group. The incidence of PONV was compared between the two groups. Results The incidence of PONV was 29% in the negative gastric suction group and 58.8% in the non-gastric suction group. The incidence of PONV in the gastric negative pressure suction group was significantly lower than that in the non-gastric negative pressure suction group, and the difference was statistically significant (p < 0.05). Conclusion By reducing the risk of perioperative bleeding in orthognathic surgery, gastric negative pressure aspiration can reduce the incidence and operation time of PONV after orthognathic surgery.